2014
DOI: 10.5194/ap-1-65-2014
|View full text |Cite
|
Sign up to set email alerts
|

TeV Cosmic Ray Anisotropy and the Heliospheric Magnetic Field

Abstract: Abstract. Cosmic rays are observed to possess a small non uniform distribution in arrival direction. Such anisotropy appears to have a roughly consistent topology between tens of GeV and hundreds of TeV, with a smooth energy dependency on phase and amplitude. Above a few hundreds of TeV a sudden change in the topology of the anisotropy is observed. The distribution of cosmic ray sources in the Milky Way is expected to inject anisotropy on the cosmic ray flux. The nearest and most recent sources, in particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Since the prediction of conventional atmospheric neutrinos from Honda et al (2007) is based on the standard US atmosphere, the expectation is corrected for annual temperature fluctuations. This is done using the formalism reported in Desiati et al (2014) and data measured by the instrument AIRS installed on the AQUA satellite (AIRS Science Team/Joao Texeira 2013). The effect of this correction is estimated to be of the order of 2% with an uncertainty of about 0.1%.…”
Section: Atmospheric Flux Uncertaintiesmentioning
confidence: 99%
“…Since the prediction of conventional atmospheric neutrinos from Honda et al (2007) is based on the standard US atmosphere, the expectation is corrected for annual temperature fluctuations. This is done using the formalism reported in Desiati et al (2014) and data measured by the instrument AIRS installed on the AQUA satellite (AIRS Science Team/Joao Texeira 2013). The effect of this correction is estimated to be of the order of 2% with an uncertainty of about 0.1%.…”
Section: Atmospheric Flux Uncertaintiesmentioning
confidence: 99%
“…In addition to this muon intensity displays a seasonal variation correlated with the temperature variations in the upper atmosphere, this was first postulated in 1952 [10]. High energy muon observations display a positive temperature dependence [11,12], where as low energy muon observations show a negative temperature dependence.…”
Section: Introductionmentioning
confidence: 84%
“…These high energies are not taken under consideration here. * Corresponing author A few explanations have been proposed, either related to interstellar magnetic field variations (Amenomori et al, 2011), intermediate turbulence (Biermann et al, 2015) due to the heliotail (Desiati and Lazarian, 2014;Zhang et al, 2014;Pogorelov et al, 2015;Schwadron et al, 2015). A detailed analysis of the power spectrum is discussed in Ahlers and Mertsch (2015) where thet authors showed that the strength of the power spectrum is related to the diffusion tensor.…”
Section: Introductionmentioning
confidence: 99%